Dielectric nanohole array metasurface for high-resolution near-field sensing and imaging - Donato Conteduca (Nature Portfolio, 2021)
Dielectric metasurfaces have different Q-factor and light localisation requirements for sensing and imaging. Here, the authors present a dielectric metasurface, supporting two optical modes with sharp Fano resonances for high Q-factors and strong spatial confinement, allowing both sensing and imaging.